CZYNNIKI OSOBOWOŚCIOWE W PROCESIE PRZYSWAJANIA I UŻYCIA JĘZYKA OBCEGO – KWESTIA EWALUACJI WYPOWIEDZI USTNEJ - Katarzyna Nosidlak (Neofilolog, 2019)
Communication in a foreign language requires activation of numerous, not necessarily linguistic, competences. As recent studies suggest, in order to facilitate this complicated process, people tend to put on different masks and change their personality-related behaviours. Such behavioural changes seem to be typical for testing situations when students’ actions are additionally influenced by stress. Drawing on her own observations and teaching experience, the author of this article strives to point to the correspondence between the manifestation of some behaviours resulting from students’ personality makeups and the effectiveness of their spoken performance in a foreign language. By directing readers’ attention to this correlation, she wants to underline the importance of personality training for the sake of effective communication in a foreign language. Additionally, this article presents the results of a survey conducted among 54 students of English at the Pedagogical University of Cracow – the data collected shows that students intentionally alter their personality-related behaviours in an attempt to earn higher scores on their oral exams. The direction of these changes might constitute useful advice for less experienced foreign-language test-takers.